Inventory Control of Single Perishable Item in Neutrosophic Environment: with Stock-based Demand, Preservation technology, Shortage and Two-stage price discount for Imperfect items - Geremew Assefa Gudeta; Natesan Thillaigovindan; Getinet Alemayehu Wole (Neutrosophic Sets and Systems)
In this article, we study an inventory model for a single perishable item which can contribute to economic growth, organizational benefit as well as individual life. Both supplier and retailer consider price discount for defective items up to a specified percentage, in a situation where the parameters involved are vague and imprecise. Such consideration has not been reported in the literature. By recognizing the power of neutrosophic environment to handle uncertainty and impreciseness inherited or existing in the problem, we use single-valued triangular neutrosophic numbers (SVNs) for representing stock-based demand, retail price, order ing cost, holding cost, wastage cost, imperfect item price, and preservation cost with de-neutrosophication. The Taylor series approximation is used to transform the time variables in the profit function into the order quantity and maximum stock variables. We determine the theoretical optimality condition and verify the concavity and uniqueness of the global optimal solution using Hessian matrix. Our aim is to determine the maximum value of the retailer’s profit by making decisions on the order quantity and maximum stock level, as well as to estimate shortages, stock-out time, cycle length, and identify the model’s inherent impreciseness. We develop neutro sophic fuzzy optimization technique ( NeFOT), an extension of the intuitionistic fuzzy optimization technique (IFOT) to evaluate the compromise acceptance, indeterminacy, and rejection levels inherited in the model and optimal solution. We support the study by illustrating a numerical example and graph with Mathematica 11.3 and LINGO 18.0.